The Effect of Perceived Value and Customer Experience on Repurchase Intention of Premium Spotify Mediated by Satisfaction - Syafrudin, M. Dholfi; Ridhaningsih, Fitria (Jurnal Economic Resource, 2025)
This study aims to analyze the influence of Perceived Value and Customer Experience on Repurchase Intention in Spotify Premium services mediated by Satisfaction. The background of this study is based on the low percentage of Spotify users in Indonesia who subscribe to premium packages, despite the number of users globally continuing to increase. The study employs a quantitative method with a survey approach, involving 150 respondents aged 17–40 years who are Spotify Premium users in the city of Padang, selected through purposive sampling. The research instrument consists of a questionnaire using a Likert scale, and data analysis is conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study indicate that Perceived Value and Customer Experience have a positive and significant effect on Satisfaction and Repurchase Intention. Satisfaction also has a positive and significant effect on Repurchase Intention, and significantly mediates the relationship between Perceived Value and Customer Experience on Repurchase Intention. These findings suggest that increasing perceived value and enhancing the positive user experience will enhance satisfaction, ultimately driving the intention to repurchase Spotify Premium. These findings have implications for Spotify Premium management, enabling the improvement of customer experience strategies and perceived value, which in turn drives satisfaction and increases repurchase intent. Additionally, the results of this study can serve as a reference for other digital service providers in designing features and services that prioritize user satisfaction.